39. PRE-SCHOOL CHILDREN CAN BE TAUGHT PATRIOTISM AND LOVE FOR THE COUNTRY - Bakhtiyorova Mashhura (Innovative technologies in construction Scientific Journal, 2023)
This article contains some information about the possibility of increasing the sense of patriotism and love for the country in children of primary school age. Measures to form children’s love for parents and country from a young age are covered.